The Effect of Employee Discipline and Commitment on Employee Performance Using the Greatday Application at PT. Jasa Raharja (Persero) - Amos Amos; Anoesyirwan Moein; Alex Zami (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The purpose of this study was to determine and analyze the effect of Discipline and Employee Commitment on Employee Performance, to identify and analyze Employee Commitment to Employee Performance, to identify and analyze Employee Discipline and Commitment to Employee Performance at PT. Jasa Raharja (Persero) Pekanbaru, Riau, Branch. The approach used in this research is an associative approach. The associative approach is an approach using two or more variables to determine the relationship or influence between one variable and another. The population in this study were all employees of the Raharja Service Company in the Pekanbaru, Riau branch office, totaling 30 people. The data collection technique in this study used a questionnaire technique. The data analysis technique in this study used Path Analysis, Partial Least Square (PLS) and Hypothesis Testing. Data processing in this study using the SmartsPLS 3.0 software program. From the research results it can be concluded that the results of the first hypothesis test indicate that the relationship between the discipline variable and employee performance has a correlation value of 0.920. The second hypothesis test results show that the relationship between the employee commitment variable and employee performance has a correlation value of 0.833. Based on the calculation results show that employee discipline and commitment have a positive effect on employee performance. This is evidenced by the R Square value of 0.853. This shows that the higher the discipline and commitment of employees, eating will have an effect on employee performance, which will be better.